Analysis of economic issues relating to the dairy sector, with emphasis on price transmission - Popovics, Péter András (Applied Studies in Agribusiness and Commerce, 2008)
The dramatic decline in consumption after 1990 was an important problem during the analysis of the sector. Even today, consumption is still below the degree that was before the political change, and significantly lags behind the EU level.The importance of this topic is emphasized by the fact that surplus milk could be marketed through the increased domestic consumption; this would create a more stable and calculable situation for farmers. Therefore, I considered it important to reveal what factors and by what shares influence the consumption of milk and dairy products. The relationship, time series and cross-sectional analysis based on national and international databases demonstrate the relationship between the consumption of milk and dairy products and the other determining factors of consumption in Hungary and in the EU-25 through diagrams. I draw the conclusion that there is a medium correlation between the development of the economy, the higher income level and the consumption of milk and dairy products. Just before our EU accession, the dairy sector was one of the most critical industries of Hungarian agriculture, which is why I chose this for my analysis. I regard as a new scientific result the econometric analysis of the asymmetric market conditions in the price transmission approach within our dairy sector between 1995 and 2003. I confirmed and quantified that the market is under an oligopoly and defined the direction of price adjustment. Furthermore, I regard as a new result in the price transmission analysis (also published in the article published with Dr. József Tóth), that the three possible dimensions (elasticity, a symmetry relations,lag) are analysed simultaneously.Therefore,a more sophisticated picture is given on price transmission. The theoretical advantages and disadvantages are verified by an example of a vertical coordination based on the horizontal cooperation in the dairy sector (Alföldi Tej Ltd).